Biochemical and cytogenetic studies of Poecilia from eastern México. I. Comparative microelectrophoresis of plasma proteins of seven species - Balsano, J. S.; Rasch, Ellen M. (Revista de Biología Tropical, 1973)
Over 2000 fisch plasmas from six species of Poecilia were collected from 33 populations in eastern Mexico and one from western Mexico. These plasmas were electrophoretically separated in 7.5% polyacrylamide gel which was stained for specific enzymes or total protein. Identiflcations of albumin band mobilities were verified by mixing isoaliquots of test plasmas with plasmas of known standards and by comparing test plasmas with plasmas from F1 hybrid progreny of known parentage. In the latipinna complex P. latipinna is polymorphic in albumin phenotype whereas P. velitera has an albumin mobility that is intermediate between two of those of P. latipinna; an unidentified petenensis-like species exhibits the slowest migrating albumin whose mobility is identical to that found in ¡he distantly related P. latipunctata. In the sphenops complex P. mexicana is polymorphic, containing five electrophoretically different albumins whereas P. sphenops tentatively appears to be monomorphic P. sphenops is characterized by two albumin bands in its plasma that are electrophoretically identical to those of northero P. mexicana and western P. latipinna.